Eco‐Friendly Electronics—A Comprehensive Review. Issue 2 (21st April 2021) - Cenci, Marcelo Pilotto; Scarazzato, Tatiana; Munchen, Daniel Dotto; Dartora, Paula Cristina; Veit, Hugo Marcelo; Bernardes, Andrea Moura; Dias, Pablo R.
Abstract: Eco‐friendliness is becoming an indispensable feature for electrical and electronic equipment to thrive in the competitive market. This comprehensive review is the first to define eco‐friendly electronics in its multiple meanings: power saving devices, end‐of‐life impact attenuators, equipment whose manufacturing uses green processing, electronics that use materials that minimize environmental and health risks, designs that improve lifespan, reparability, etc. More specifically, this review discusses eco‐friendly technologies and materials that are being introduced to replace the well‐established ones. This is done for all material classes (metals, polymers, ceramics, and composites). Manufacturing, recycling, and final product characteristics are discussed in their various interconnected aspects. Additionally, the concept of consciously planned obsolescence is introduced to address the paradoxical relationship between durability and efficiency. The overall conclusions are that there is an important global trend to make electronics more eco‐friendly. However, matching the performance and stability of well‐established materials and technologies seems to be the main barrier to achieve it. These new implementations can have detrimental or beneficial net impacts on the environment. Assessing their net outcome is challenging because their impacts are frequently unknown and the current evaluation methods (and tools) are incapable of comprehensively quantifying these impacts and generating reliable verdicts. Abstract : This review presents the multiple aspects that characterize eco‐friendly electronics. Alternative materials, greener manufacturing, recycling methods, consumers' awareness, and end‐of‐life strategies must be perfectly geared to truly represent eco‐friendliness. Nevertheless, each matter embodies a more complex reality. Despite the notoriety of the subject, the current assessments are insufficient to quantify the net impact of eco‐friendly actions on the environment.